Pharmaceutical Preparation of Abhraka Bhasma: A Classical Approach Covering all Stages of Processing (AYUSHDHARA, 2025)
Abhraka (mica) is essential in Rasashastra for its Rasayana properties and therapeutic applications. However, its raw form is unsuitable for direct medicinal use. To make it safe, effective, and easy for the body to absorb, it goes through special Ayurvedic processes. These include Shodhana, Dhanyabhraka, Marana, Amritikarana, and Lohitikarana. Materials and Methods: Raw Abhraka underwent sequential procedures Shodhana, Dhanyabhraka, Marana, Amritikarana, and Lohitikarana. Observations were recorded for changes in weight, texture, color, and classical parameters such as Nischandratva, Rekhapurnata, and Varitaratwa. Results: Shodhana caused 9.8% weight loss with improved brittleness and reduced impurities. Dhanyabhraka showed 23.83% weight loss, effective leaching, and pH reduction. Marana led to a 14.7% weight loss with color transition from blackish red to dull red. Amritikarana enhanced stability and reduced toxicity, while Lohitikarana imparted a red tinge and improved therapeutic potential. The final Bhasma was non-lustrous, floatable, and therapeutically active. Discussion: Stepwise processing confirmed the classical principles of Rasashastra, validating Ayurvedic principles of purification and incineration, ensuring safety, bioavailability, and Rasayana potential.